Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.joca.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

‘Acute flare-ups’ in patients with, or at high risk of, knee osteoarthritis: a daily diary study with case-crossover analysis

Abstract: 19Objective: To determine the natural history of flare-ups in knee osteoarthritis and their 20 relation to physical exposures. 21 22 Design: Adults aged ≥45 years with a recent primary care consultation for knee 23 OA/arthralgia completed a daily pen-and-paper diary for up to 3 months, including 24 questions on average knee pain intensity, pain descriptors, other symptoms, activity 25 interference, and selected physical exposures (prolonged kneeling, squatting, climbing 26 stairs, ladders, and movin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 12 publications
5
25
0
1
Order By: Relevance
“…The direction of our observed associations with exposure to one or more physical activities is consistent with previous study 35 , as is our positive association with knee buckling. 37 More broadly, our observed associations with a range of physical and psychosocial exposures are consistent with previous study of back pain 9 , knee/hip OA 10 , knee OA 11,13 and hip OA 12,38 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The direction of our observed associations with exposure to one or more physical activities is consistent with previous study 35 , as is our positive association with knee buckling. 37 More broadly, our observed associations with a range of physical and psychosocial exposures are consistent with previous study of back pain 9 , knee/hip OA 10 , knee OA 11,13 and hip OA 12,38 .…”
Section: Discussionsupporting
confidence: 93%
“…Previous work by Marty et al 46 showed clearly that patient-identified flares agreed well with clinician-defined flares. The similarity of findings with others 11,13,35,37 also provide some valuable replication and suggest that these associations may not be too highly sensitive to this choice of flare definition. Other signs and symptoms, for example, stiffness, swelling and functional impact may be earlier or more important initial symptoms associated with flare onset.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 75%
See 1 more Smart Citation
“…This may be explained by a high false-positive rate of detecting effusion on clinical examination, as well as the fact that imaging for this study was not performed at the time of the clinical diagnosis of synovitis. Moreover, OA is characterized by so-called "flare-ups", sudden and temporary increases in symptoms along with exacerbations of synovitis [18,19], and it is possible that the degree of synovitis at the time of imaging was lower than during clinical examination. However, since our analyses focused on comparison of imaging techniques within the same patient exactly at the same time point, we expect that this will not have affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…Е. Parry и соавт. [21] оценивали частоту и продолжительность рецидивов ОА у 67 больных, которые фиксировали обострения заболевания в дневнике. В течение месяца обострение ОА возникло у 30 (45%) больных, причем у 16 из них -лишь одно, у 6 -два, у 6 -три, у 2 -четыре; длительность обострения составляла в среднем 8 дней (от 3 до 30).…”
Section: безрецептурные нестероидные противовоспалительные препараты unclassified